Development of Creative Economy through Participatory Rural Appraisal (PRA) in Sedayung MSMEs - Nuraini Asriati; Sandra Fitria Wardani; Munawar Thoharudin (Universitas Pendidikan Ganesha, 2025)
The creative economy is pivotal in driving economic growth, fostering innovation, and creating jobs, particularly in rural areas. This study explores the significance of community participation in developing the creative economy by applying the Participatory Rural Appraisal (PRA) approach in Teriak District, Bengkayang Regency. A qualitative research design was adopted, incorporating interviews, observations, and document analysis to provide in-depth insights into community participation patterns and challenges. The PRA method was selected for its ability to facilitate active community involvement in identifying local economic potentials and challenges, enabling the formulation of inclusive and context-specific development strategies. The findings indicate that PRA has successfully enhanced community involvement in critical areas of creative economy development, such as improving digital literacy, providing continuous mentoring, and expanding access to capital and technology. However, significant challenges persist, including low participation in marketing activities, inadequate infrastructure, and limited collaboration between the government and local communities, which hinder the overall effectiveness of the initiatives. Community engagement varies across different activities, with active participation in production processes but limited involvement in marketing and decision-making. Social and economic factors strongly influence these participation patterns, with community cohesion and relevant skill sets playing a crucial role in driving innovation and market adaptability. This study underscores the importance of aligning development strategies with local needs and potentials to promote inclusivity and sustainability. While the PRA approach proves effective in fostering community-driven initiatives, enhancing digital literacy and ensuring equitable access to resources is essential to maximizing its impact. Despite limitations related to the study's regional focus and qualitative approach, it provides valuable insights into the role of participatory methods in supporting creative economy growth. Addressing structural and social barriers will pave the way for broader and more meaningful community engagement, ultimately bolstering economic resilience and self-reliance in rural areas.